Dinâmica e indução do olhar : implicações estéticas da estratégia curatorial - Ramos, Sandra Isabel Direito (2021)
This dissertation presents both the role of the subject in relation to the arts, as well as that of the curator, in order to understand the evolutionary relationship between the two and how this relationship with the pieces of art is managed. The approach to the problem will be made through the historical moment that is given the appreciation of the subject, which consists of the birth of aesthetics, the study of the beautiful, the acquiring of taste, contemplation of the sublime and finally the understanding of the aesthetic experience. With the arrival of these mechanisms of appreciation of the subject, the conception of art as well as its exhibition changes, therefore, the artistic objects that follow aim at a relationship with the public and, in some cases, an awareness of its denial. This world that relates with the receiver and the form of reception enters into a sphere of subjectivization, creating a series of microworlds and endless alternatives. Art separates itself from the representations with religious and historical themes, starting to elevate senses and seeking to provoke experiences on the observer or, in other words, to stimulate the senses in the one who observes. Art ceased to have its limits visible and became an open space for discussion, this attitude provoked a need for the existence of an entity that is capable of discerning what art is, according to the new dilemmas, and "why", so the role of the curator expands, and he creates the spectacle of art. This spectacle of art interferes in the dynamic between the public and the pieces of art that are exhibited, in other words, the curator becomes the mediating figure between the relationship of the subject who observes and the piece of art that is observed, leading the observer, using certain curatorial strategies. In this way, the subject's relationship with the works and the curator's intervening role are problematized, so that an evolutionary understanding of the relationship between the two is possible and how this connection with the work is induced. Two examples of exhibitions that differ from each other were selected for analysis, where the induction through a curatorial strategy is evident and assumed, whether through reports, speeches or records: — Two historical exhibitions, Entartete Kunst and Mark Rothko, considering that they present the two extremes that represent two typologies of curatorial strategy whose purpose to induce is, on the one hand positive and, on the other, negative in relation to the result caused in the reception by the subject.The analysis of the curator's work in some selected exhibitions exposes the various strategies used, revealing the process, and understanding the limits and responsibilities of the curator. In other words, it translates into the study of curatorial practice that is based on two specific cases of curatorship analyzing and detecting in what way the observer is induced, questioning the curator’s conveyance, that is, to what extent the piece of art is denoted, or if it loses its real aggregate sense? Essentially, it is a weighting on the relation between the curator and a piece of art, likewise the aesthetic implications from this induction.